Microsatellite Identification in Solanaceae Crops Associated with Nucleoside Diphosphate Kinase (NDK) Specific to Abiotic Stress Tolerance through in silico Analysis - Reena Rosy Thomas; M K Chandra Prakash; M Krishna Reddy; Sukhada Mohandas; Riaz Mahmood (Journal of Horticultural Sciences, 2013)
Abiotic stress often causes a series of morphological, physiological, biochemical and molecular changes that affect plant growth, development and productivity. To cope with abiotic stresses, it is necessary to understand plant responses to stresses that disturb homeostatic equilibrium at the cellular and molecular level. Genomic information on Capsicum annuum has been explored to identify microsatellite markers associated with abiotic stress tolerance and assign them to cognate functional groups related to specific stress responses. Several in silico methods have been used to identify simple sequence repeats associated with stress responsive gene candidates in Capsicum annuum. In this study, a microsatellite marker has been identified in Capsicum annuum associated with Nucleoside Diphosphate Kinase (NDK) having multiple environmental stress tolerance (oxidative, high temperature and salt stress) and which is also highly conserved in crops of Solanaceae. These are house-keeping enzymes that maintain intracellular levels of all nucleoside triphosphates (NTP) with the exception of adenosine triphosphate (ATP). These are also involved in phytochrome A response, UV-B signaling, auxin responses and oxidative stress signaling.